Women’s Issues in Liberal Thought: The Verses of Inheritance as a Model - Al-Mutairi, Mona Saud (Journal of Islamic Sciences, 2023)
The idea of the research is based on unveiling women’s issues in liberal thought, specifically in the verses of inheritance, and clarifying the most important liberal starting points in their view of women’s inheritance, and he listed some of the applications of liberal Arabs in their interpretation of the verses of inheritance, and a statement of Islam’s position on women’s inheritance, In my study, I relied on two approaches: the inductive approach, and the critical approach. In my research, I talked about liberal principles in their view of women’s inheritance, And the applications of Arab liberalism in the interpretation of the verses of inheritance, and the position of Islam on women’s inheritance, And I came out of this research with results, the most important of which is that the liberals’ view of women’s inheritance stems from purely material foundations and principles, The attempts of liberalism to interpret the verses of inheritance aim to distort the status of women in Islam, And that Islam’s position on women’s inheritance is that it gave her rights according to certain standards and different cases that govern the division of inheritance.